PENGARUH CITRA MEREK DAN KEMASAN PRODUK TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA CV. SIBOLGA NAULI MADANI - Yenni Sofiana Tambunan (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
This study entitled "The Effect of Brand Image and Product Packaging on Consumer Purchasing Decisions on CV. Sibolga Nauli Madani. The purpose of this study was to determine the effect of brand image and packaging on consumer purchasing decisions on CV. Sibolga Nauli Madani. The population in this study were 30 consumers who were taken randomly and simultaneously became the research sample. Primary data collection is done through a questionnaire, where before the questionnaire was distributed, a validity and reliability test was conducted on the questionnaire. The results showed that all data entered in the model were normally distributed as indicated by bell histogram graphs and normal PP standarized residual graphs showing all residual data points in the three variables following the diagonal line data on the scater plot and Kolmogorov Smirnov's testistic analysis showing z values ​​of 0.852 <from Z α 5% which is 1.97 and the probability value is 0.461> 0.05. The Heteroscedacity and multicolineirity problems are not found in the model, which shows points scattered randomly and both above and below zero on the Y axis. Tolerance values ​​are independent variables 0, 661 and 0.661 above 0.1 and the Variance Inflation Factor1 value, respectively. 513 and 1,513 do not exceed 10. Hypothesis testing simultaneously shows that brand image and packaging have a positive and significant effect on consumer purchasing decisions on CV. Sibolga Nauli Madani.